2001
DOI: 10.1080/02652030010027624
|View full text |Cite
|
Sign up to set email alerts
|

ICP/MS and ICP/AES elemental analysis (38 elements) of edible wild mushrooms growing in Poland

Abstract: Thirty-eight elements, including toxic cadmium, lead, mercury, silver and thallium, were determined in 18 species of wild edible mushrooms collected from several sites in Pomorskie Voivodeship in northern Poland in 1994. Elements were determined by double focused high resolution inductively coupled plasma mass spectrometry (HR-ICP-MS) and inductively coupled plasma atomic emission spectroscopy (ICP-AES), after wet digestion of the dried samples with concentrated nitric acid in closed PTFE vessels using a micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
47
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(56 citation statements)
references
References 14 publications
8
47
1
Order By: Relevance
“…Mostly, Fe concentrations are in the range of 50-150 ppm. This range agrees satisfactorily with most literature data Quinche 1980aQuinche , b, 1981Quinche , 1983aQuinche , 1987Quinche , 1988aQuinche , b, 1990Tyler 1980;Kalač et al 1989;Vetter 1990;Valiulis et al 1995;Demirbaş 2001;Falandysz et al 2001;Nikkarinen and Mertanen 2004;Rudawska and Leski 2005a, b). Somewhat higher values were reported by Vetter (2005) for certain Amanita species.…”
Section: Ironsupporting
confidence: 86%
See 1 more Smart Citation
“…Mostly, Fe concentrations are in the range of 50-150 ppm. This range agrees satisfactorily with most literature data Quinche 1980aQuinche , b, 1981Quinche , 1983aQuinche , 1987Quinche , 1988aQuinche , b, 1990Tyler 1980;Kalač et al 1989;Vetter 1990;Valiulis et al 1995;Demirbaş 2001;Falandysz et al 2001;Nikkarinen and Mertanen 2004;Rudawska and Leski 2005a, b). Somewhat higher values were reported by Vetter (2005) for certain Amanita species.…”
Section: Ironsupporting
confidence: 86%
“…However, extraordinarily high Fe content (our data: 1,304-2,075 ppm) is found in Suillus variegatus (Drbal et al 1975;Kalač et al 1989;Valiulis et al 1995;Falandysz et al 2001). This species is known to concentrate this element.…”
Section: Ironmentioning
confidence: 94%
“…Interestingly, Se content in wild edible mushroom species has been widely studied [12][13][14][15]. These organisms have previously been shown to effectively accumulate different biologically essential elements such as potassium [16][17][18] and contain significant levels of riboflavin and niacin. Unfortunately, various studies have shown that mushrooms can also contain toxic metals such as mercury or cadmium, but this was attributed only to those species which grow on polluted sites and contaminated substrates.…”
Section: Introductionmentioning
confidence: 98%
“…Elevated total mercury concentrations have been measured in this species in other studies: 0.89-1.0, 4.9 § 3.1, 1.1 § 0.2, and 5.3 § 0.8 (Poland), 5.0 (Germany), 3.1 § 1.5 to 9.0 § 0.4 (Austria), 1.8 § 0.1 to 4.7 § 0.0 (Hungary), 2.0-6.0 (Slovenia), 0.96 (Finland) and 1.5 § 0.7 mg/kg dry matter (Spain) (Aichberger 1977;Byrne and Ravnik 1976;Falandysz and Chwir 1997;Falandysz et al 1996Falandysz et al , 1999Falandysz et al , 2000Falandysz et al , 2001Falandysz et al 2002Kuusi et al 1981;Lasota and Witusik 1987;Seeger, 1978;Vetter and Berta, 1997;Zurera et al 1987).…”
Section: Resultsmentioning
confidence: 96%
“…The wellknown example is Fly Agaric (Amanita muscaria), which is rich in vanadium in the form of the organovanadium compound amavadine, the Amethyst Deceiver (Laccaria amethistina), rich in arsenic found in arsenobetaine and some other compounds, the Goat's Foot (Albatrellus pes-caprae), rich in selenium found in several selenocompounds, the Variegated Bolete (Suillus granulatus), rich in iron, and Amanita strobiliformis, found recently to be particularly rich in silver (Koch et al 1987;Stijve and Bourqui 1991;Stijve et al 1998;Falandysz et al 2001;Borovibka et al 2007). The genetic and ecological factors (age of mycelium, yield of fruiting bodies, soil substrate characteristic), in addition to certain poorly known factors (abundance and bioavailability of elements and the impact of their oxidation state or chemical form in the substrate on bioconcentration potential or exclusion, possibility of biomethylation of some elements by mushroom and enhanced accumulation of methylated species in the Xesh; abundance of possible ligands in fruiting body including sulfhydryl groups, disulWdes or methionine; passive or active uptake; and for many species also the impact of mycorrhiza) determine the ability of mycelium (hyphae) to absorb, translocate, and accumulate many elements at relatively high concentrations in the fruiting bodies of higher fungi (Aichberger 1977;Zurera et al 1986).…”
Section: Introductionmentioning
confidence: 97%